Rate-splitting scheme and its achievable sum-rate for the symmetric cyclic Gaussian interference channel - Bo ZHANG; Yong LI; Bao-ming BAI; Xiao MA (Tongxin xuebao)
By analyzing the performance of Han-Kobayashi (HK) strategy in the N-user cyclic Gaussian symmetric in-terference channel, an adaptive odd-even symmetric rate-splitting scheme was proposed to reduce the complexity and in-crease the sum-rate to the inner bound of HK, which contains various schemes based on rate-splitting and optimal split ratio. Numerical simulation results of symmetric scheme in the high SNR and the general SNR regimes indicate that, in wide range of transmitted power and interference factor, the sum-rate achieved using adaptive rate-splitting scheme is higher than that achieved using the scheme proposed by Tse et al., and approaches the inner bound of HK scheme in the general SNR regimes.